Does Selective Posterior Correction and Fusion Surgery Influence Cervical Sagittal Alignment in Patient with Lenke Type 5 Adolescent Idiopathic Scoliosis?—A 5-year Follow-up Retrospective Cohort Study. Issue 18 (15th September 2021) - Okubo, Toshiki; Yagi, Mitsuru; Suzuki, Satoshi; Nori, Satoshi; Tsuji, Osahiko; Nagoshi, Narihito; Okada, Eijiro; Fujita, Nobuyuki; Nakamura, Masaya; Matsumoto, Morio; Watanabe, Kota
Abstract : Study Design: A retrospective comparative study. Objective: The aim of this study was to examine the changes in cervical sagittal alignment (CSA) following surgical correction in a patient with Lenke type 5 adolescent idiopathic scoliosis (AIS) and evaluate any possible factors influencing postoperative CSA. Summary of Background Data: Few studies have assessed the association between CSA and thoracic or lumbar sagittal alignment in AIS patients with major thoracolumbar/lumbar curve who underwent posterior correction and fusion surgery. Methods: Sixty-six patients with Lenke type 5 AIS (two males and 64 females, the mean age at surgery of 16.2 years) were included in this study. They were followed up for minimum 5 years after surgery. Multiple linear regression analysis was used to evaluate possible factors influencing the postoperative CSA. To determine the influence of upper end vertebra (UEV) level on postoperative CSA, the subjects were divided into two groups according to UEV level of ≥T9 or ⩽T10. The outcome variables were compared between the two groups and analyzed for changes in various spinal sagittal profiles using radiographic outcomes. Results: Multiple linear regression analysis revealed that preoperative T10-L2 kyphosis and LL were significantly correlated with postoperative C2–7 lordosis. However, CSA did not significantly change at 5 years after surgery. Sub-analysis of the cohort revealed that in the UEV ≥T9 group, the mean thoracic kyphosis significantly increased from 20.3° ± 10.6° to 24.0° ± 8.9° and the mean C2–7 lordosis also significantly increased from −12.5° ± 8.3° to −4.3° ± 10.3° at 5-year postoperatively. SRS-22 outcomes were comparable between the groups. Conclusion: We indicated that the CSA was not influenced by surgical correction in most Lenke type 5 AIS patients. However, in a patient whose UEV was located at T9 or higher levels, CSA was influenced through the changes in thoracic kyphosis following posterior correction surgery. Level of Evidence: 4 Abstract : Supplemental Digital Content is available in the textThe cervical sagittal alignment did not significantly change after surgical correction in most Lenke type 5 adolescent idiopathic scoliosis patients. However, in the patients whose upper end vertebra was located at T9 or higher levels, the C2–7 lordosis significantly increased along with the increases of thoracic kyphosis after posterior correction surgeries.